2010
DOI: 10.1038/ajh.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Free Leptin Predicts Incident (Clinic) Hypertension in a Danish Cohort

Abstract: Study" 1 that investigated the independent effects of leptin and adiponectin on incident hypertension in a large Danish populationbased cohort. The authors have elegantly shown that leptin, but not adiponectin, was an independent predictor of new-onset (clinic) hypertension.An issue not taken into account by the Danish study is that participants were not screened for obstructive sleep apnea syndrome (OSAS), a well-associated comorbidity with both free leptin and new-onset hypertension. Although the exclusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…observed that free leptin predicts incident hypertension in a Danish cohort. 39 Leptin may regulate blood pressure through sympathetic activation. 40 In our study, we found elevated plasma leptin level was associated with systemic hypertension: mean leptin was significantly higher in hypertensive than normotensive individuals ( P = 0.014) (Figure 1), as well as in subjects with positive family history of hypertension ( P = 0.035) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…observed that free leptin predicts incident hypertension in a Danish cohort. 39 Leptin may regulate blood pressure through sympathetic activation. 40 In our study, we found elevated plasma leptin level was associated with systemic hypertension: mean leptin was significantly higher in hypertensive than normotensive individuals ( P = 0.014) (Figure 1), as well as in subjects with positive family history of hypertension ( P = 0.035) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%